Alliance of Ummah in Rural Areas: A New Perspective on Islamic Populism in Indonesia - Rojabi Azharghany; Hotman Siahaan; Akh. Muzakki (UIN Sunan Gunung Djati Bandung, 2020)
Islamic populism in Indonesia is perceived as an alliance of the people on behalf of the ummah in urban areas, against the ruling elites who enjoy the promises of peace and prosperity more than capitalism, modernism and democracy. This paper though intends to disclose the Islamic populism in rural areas through the power of capital and symbols as part of the cultural heterogenity between alliances in rural areas and large cities that simply focuses on political power. This research embraces the socio-cultural approach by applying the theory of generative structuralism penned by Pierre Bourdieu in order to analyze the resistance of cultural heterogenity by invigorating the cultural reproduction and symbols dominance to thwart the ummah alliance in urban areas. The results of this research show that the Islamic populism in rural areas upholds the belief in salvation, peace and unity, by reinforcing the cultural heterogenity among the congregations on various bases. In spite of domestication process in Islamic populism by the ruling elite, the ummah alliance in rural areas cannot be triggered due to their firm belief in salvation, which differs from the Islamic populism in large cities where a symbol of injustice of the bourgeoisie and the ruling elites prevails. The Islamic populism in rural areas has caused the failure of Islamic populism in large cities since their main discourse solely considers the middle class, in contrast to the Islamic populism in rural areas that might may welcome both the middle class and the lower class.